2018
DOI: 10.1111/ejn.14160
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and alcohol: the role of midbrain dopaminergic neurons in drug reinforcement

Abstract: Nicotine and alcohol addiction are leading causes of preventable death worldwide and continue to constitute a huge socio‐economic burden. Both nicotine and alcohol perturb the brain's mesocorticolimbic system. Dopamine (DA) neurons projecting from the ventral tegmental area (VTA) to multiple downstream structures, including the nucleus accumbens, prefrontal cortex, and amygdala, are highly involved in the maintenance of healthy brain function. VTA DA neurons play a crucial role in associative learning and rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 380 publications
0
24
0
Order By: Relevance
“…Like cocaine and opioids, DA release has been heavily implicated in the reinforcing effects of alcohol [68–70]. Though the precise mechanisms remain poorly understood, there is evidence suggesting that alcohol increases DA neurotransmission by increasing the activity of VTA DA neurons [68,71–73]. Interestingly, while this increased activity of VTA DA neurons in response to alcohol leads to large DA release in the NAc, the NAc shell exhibits larger transient increases in DA compared to the core, consistent with other drugs of abuse [30,32,59,60].…”
Section: Medial Vta‐mnacsh Da Release and Sudsmentioning
confidence: 81%
See 1 more Smart Citation
“…Like cocaine and opioids, DA release has been heavily implicated in the reinforcing effects of alcohol [68–70]. Though the precise mechanisms remain poorly understood, there is evidence suggesting that alcohol increases DA neurotransmission by increasing the activity of VTA DA neurons [68,71–73]. Interestingly, while this increased activity of VTA DA neurons in response to alcohol leads to large DA release in the NAc, the NAc shell exhibits larger transient increases in DA compared to the core, consistent with other drugs of abuse [30,32,59,60].…”
Section: Medial Vta‐mnacsh Da Release and Sudsmentioning
confidence: 81%
“…Like cocaine and opioids, DA release has been heavily implicated in the reinforcing effects of alcohol [68–70]. Though the precise mechanisms remain poorly understood, there is evidence suggesting that alcohol increases DA neurotransmission by increasing the activity of VTA DA neurons [68,71–73].…”
Section: Medial Vta‐mnacsh Da Release and Sudsmentioning
confidence: 99%
“…Importantly, the high‐affinity α4β2 is most densely expressed on dopaminergic VTA neurons while the α7‐homomeric nAChRs are primarily located on excitatory glutamatergic terminals that synapse on dopamine neurons. Both of which have been demonstrated to increase dopamine signaling via activation by EtOH and/or NIC (reviewed in Morel et al ). Evidence suggests that EtOH may potentiate the actions of most nAChRs while inhibiting nicotine‐induced receptor desensitization (Aistrup et al ; Marszalec et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The dopamine transmission from the VTA into the nucleus accumbens regulates the rewarding system and involves addiction behaviour 29 and anxiety behaviour. 8 Previous report suggested that ethanol actions in the VTA increase in the rewarding responses. Chronic ethanol intoxication produces opposite effects of acute ethanol intoxication and/or compensatory/homeostatic effects on the expression, localisation, and function of proteins.…”
Section: Resultsmentioning
confidence: 98%